Banking, business and race : the Kwong Yik Bank in colonial Singapore and the Malay States - Goh, Jeremy (Nanyang Technological University, 2021)
In 1903, a group of ten Cantonese businessmen and one Peranakan comprador formed the Kwong Yik Bank (KYB), the first “modern” incorporated bank in Singapore and Southeast Asia. It was a short-lived venture, having collapsed after ten years of operation. The KYB’s failure resulted in a protracted liquidation process that took another decade to complete, two lawsuits against its Assistant Managing Directors, public criticism against the supposed failings of the organizational structures and behavior of “Chinese” enterprise, as well as the British colonial state’s laxity in enforcing the Companies Ordinance. In response, the state tightened regulations on the finance and business sectors through amendments to the Companies Ordinance, which were vehemently opposed by the European non-official members to a greater extent than their Chinese counterparts in the Legislative Council.